Metabolism of endogenous nutrients in islets of Goto-Kakizaki (GK) rats. - Sener, A (1993)
The metabolism of endogenous nutrients was examined in pancreatic islets of control and Goto-Kakizaki (GK) rats. At the ultrastructural level, no glycogen was found in the islet cells of GK rats, a situation similar to that prevailing in normal islets. Likewise, by measuring the output of L-lactate from islets first incubated at 16.7 mM D-glucose and then at 2.8 mM D-glucose, no evidence of glycogenolysis was found in the islets of GK rats. The production of NH4+ and that of 14CO2 from islets prelabelled with either L-[U-14C]glutamine or [U-14C]palmitate were higher, however, in GK than in control rats. The changes in NH4+ and 14CO2 production evoked by D-glucose, by a non-metabolized analogue of L-leucine (2-amino-bicyclo[2,2,1]heptane-2-carboxylic acid; BCH) and by 3-phenylpyruvate were qualitatively comparable in control and GK rats. The secretory response to these three secretagogues was severely decreased in the islets of GK rats. This coincided with an impaired enhancing action of D-glucose on the conversion of [2-3H]glycerol into 3HOH. It is concluded that the catabolism of endogenous amino and fatty acids in islets is greater in GK than in control rats, especially at low D-glucose concentration. This may account, in part at least, for the altered secretory response to BCH and 3-phenylpyruvate. For glucose-induced insulin release, however, an impaired acceleration of the glycerol phosphate shuttle apparently also participates in the secretory defect.